EXPERIENCE OF PATIENT'S FAMILY MEMBERS DURING RESUSCITATION OF LOVED ONES IN ADULT ICU OF TERTIARY CARDIAC CARE HOSPITAL: A QUALITATIVE STUDY (The Research of Medical Science Review, 2025)
Background: Though family members' attendance during resuscitation in the adult intensive care unit is an essential component of patient care, little is known about the emotional and psychological effects on families. Objective: This study aims to explore the lived experiences of family members who are usually present during resuscitation in the tertiary cardiac care hospital the emotional responses and coping strategies to their perceptions of care. Methodology: A qualitative research design was applied to 15 family members of patients undergoing resuscitation in the ICU involving in-depth interviews. Result The thematic analysis of the interview data indicated that, for the outcomes of the procedure, family members had had many emotions ranging from fear and confusion to grief and relief. The coping mechanisms were different as emotional support from health care providers and religious practices proved to be major sources of comfort. Conclusion: Family-centered care, characterized by effective communication, support- emotional provision, and cultural sensitivity, would be the most effective measures to heighten the emotional experience of families during resuscitation.